1997
DOI: 10.1039/a606135d
|View full text |Cite
|
Sign up to set email alerts
|

Structures of 9,10-dihydro-9-heteroanthracenes and 9,10-dihydro-9-heteroanthracenide anions; an ab initio MO calculation

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…The NMR data for potassium xanthenide (10) agree well with those recorded for this salt in liquid ammonia (15) if one allows for the solvent effect. Moreover, we have shown that there is good agreement between the observed 13 C chemical shifts and the calculated (ab initio) charge distributions for a completely flat xanthenide anion and that this species may be classified as an example of an extensively delocalized 16 pi-electron system (16 ). In the case of DHA, treatment of the hydrocarbon with an excess of K + DMSYL-d 6 ᎑ in DMSO-d 6 results in the formation of monoanionic species DHA ᎑ and no DHA 2᎑ is observed.…”
Section: R-h + R′supporting
confidence: 56%
See 1 more Smart Citation
“…The NMR data for potassium xanthenide (10) agree well with those recorded for this salt in liquid ammonia (15) if one allows for the solvent effect. Moreover, we have shown that there is good agreement between the observed 13 C chemical shifts and the calculated (ab initio) charge distributions for a completely flat xanthenide anion and that this species may be classified as an example of an extensively delocalized 16 pi-electron system (16 ). In the case of DHA, treatment of the hydrocarbon with an excess of K + DMSYL-d 6 ᎑ in DMSO-d 6 results in the formation of monoanionic species DHA ᎑ and no DHA 2᎑ is observed.…”
Section: R-h + R′supporting
confidence: 56%
“…4) lacking signals due to the carbanionic centers (carbon C-9). Such signals appear at 68.9 and 72.1 ppm, respectively, in the KNH 2 /NH 3 (ᐉ) system (15,16 ). The disappearance of the carbanionic carbon signal may be explained by considering that such centers, which are deuterated owing to H-D exchange, give rise to weak multiplets (especially for molecules of this size), which may be lost in spectral noise (18).…”
Section: R-h + R′mentioning
confidence: 99%
“…10-Methylacridan and its derivatives are not planar molecules and, according to calculations, may undergo a substantial geometry change after ionization. The B3LYP/6-31G* method predicts that the dihedral angle Φ between two aromatic side rings is 148.11° (compared to 142.7° from HF SCF calculations 14 ) and 149.21° in neutral 3H and 1H , respectively. , The geometry changes on ionization and the resulting radical cations are more planar than their neutral parent compounds: Φ = 161.96° ( 3H • + ) and 165.29° ( 1H • + ).…”
Section: Resultsmentioning
confidence: 99%